2007
DOI: 10.2320/jinstmet.71.985
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Distribution of Local Critical Current to Overall Critical Current in Bi2223 Superconducting Composite Tape Damaged by Bending

Abstract: The damage extent and therefore the critical current are different from position to position in a long sample especially when the sample is deformed severely. In the present work, a 48 cm long Bi2223 composite tape bent by 0.7, being composed of 48 elements with a length of 1 cm and of 8 parts with a length of 6 cm, was used as the test sample. The V I curve, critical current and n value were measured for the 48 elements, 8 parts and overall sample, and the relation of the distribution of the critical curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As an alternative distribution function that enables us to describe the distribution of the local critical current at ε B = 1.1% where the ln ln(1 − F) −1 versus ln(I c ) plot showed a concave shape (figure 5(d)), the bimodal Weibull distribution can be mentioned [26,31,41,42]. It has been found in our preceding work that this function can describe the experimental results at high ε B (≈1.0%) for the samples from other suppliers [26,31,41]. In the present work, as well as in our preceding work, it was attempted to apply the bimodal Weibull distribution function to the experimental results at ε B = 1.1%.…”
Section: Analysis Of the Distribution Of Local And Overall Critical C...mentioning
confidence: 99%
“…As an alternative distribution function that enables us to describe the distribution of the local critical current at ε B = 1.1% where the ln ln(1 − F) −1 versus ln(I c ) plot showed a concave shape (figure 5(d)), the bimodal Weibull distribution can be mentioned [26,31,41,42]. It has been found in our preceding work that this function can describe the experimental results at high ε B (≈1.0%) for the samples from other suppliers [26,31,41]. In the present work, as well as in our preceding work, it was attempted to apply the bimodal Weibull distribution function to the experimental results at ε B = 1.1%.…”
Section: Analysis Of the Distribution Of Local And Overall Critical C...mentioning
confidence: 99%
“…The frequency (probability density) calculated by equation ( 3) with the obtained parameters stated above is presented in figure 6, describing the measured one. The authors are carrying out similar experiments not only for the present sample but also for a different fabricationroute Bi2223-composite tape sample [32]. Recently, it was found that, when the sample is significantly damaged as in the present case for 1.0% bending, equation ( 3) is a useful tool for the description of the local critical current distribution.…”
Section: Statistical Analysis Of the Distribution Of The Critical Cur...mentioning
confidence: 74%
“…On the other hand, the curve of 1.0%-bent elements with a downward convex shape in figure 5(a) indicates that, when the applied bending strain is high, equation ( 2) is not suitable for the description of the distribution. As an alternative distribution that enables us to describe the distribution of 1.0%bent elements, the multimodal Weibull distribution can be mentioned [31,32]. This function stems from the competing risk model and is applicable when plural causes of damage coexist.…”
Section: Statistical Analysis Of the Distribution Of The Critical Cur...mentioning
confidence: 99%
See 1 more Smart Citation
“…͑3͒ later͔. 24,37 The applicability of the three parameter and bimodal functions to the present experimental results ͑Fig. 3͒ was examined as follows.…”
Section: Distributions Of Measured Local and Overall Critical Cumentioning
confidence: 99%